1984
DOI: 10.1099/0022-1317-65-3-525
|View full text |Cite
|
Sign up to set email alerts
|

Production of Monoclonal Antibodies to Viruses in the Potyvirus Group: Use in Radioimmunoassay

Abstract: SUMMARYHybridomas were developed that secreted antibodies to soybean mosaic (SMV), lettuce mosaic (LMV) viruses, and to maize dwarf mosaic (MDMV) virus, strains Ap and B. All hybridomas produced antibodies specific to the homologous virus except for one to LMV, which produced antibodies that reacted at a low level with SMV and MDMV. Monoclonal antibodies against SMV were used in a double-antibody sandwich radioimmunoassay. The assay using only one type of monoclonal antibody lacked sensitivity because, presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…These results are slightly different from those of Hill et al (1984) who used a radioimmunoassay for soybean mosaic virus that involved both rabbit polyclonal antibody and In column 1, WSBMV was spotted at 1600 ng/ml; infected and control at 1 g/4 ml TBS. The spots were purple in WSBMV and infected rows indicating a positive reaction, and green in control row indicating a negative reaction.…”
Section: Comparisons Of Elisas Employing Polyclonal Antibodies And/orcontrasting
confidence: 50%
“…These results are slightly different from those of Hill et al (1984) who used a radioimmunoassay for soybean mosaic virus that involved both rabbit polyclonal antibody and In column 1, WSBMV was spotted at 1600 ng/ml; infected and control at 1 g/4 ml TBS. The spots were purple in WSBMV and infected rows indicating a positive reaction, and green in control row indicating a negative reaction.…”
Section: Comparisons Of Elisas Employing Polyclonal Antibodies And/orcontrasting
confidence: 50%
“…Although the sensitivity of the double-sandwich ELISA systems is quite high, their utility for quantitative assays of a large range of naturally occurring SMV strains is limited (Chen et al, 1982) due to putative alterations in the antibody combining site (Koenig, 1978). SPRIA systems using a 3H-labelled detecting antibody are sensitive and possess a broad cross-reactivity for different SMV isolates (Bryant et al, 1983;Hill et al, 1984) but require disposal of radioactive waste liquids and frequent conjugation because of decreasing specific activity of the labelled detecting antibody during storage (J. H. Hill, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal antibodies (M-Ab) produced by somatic cell hybridization (K6hler & Milstein, 1975) have great potential for plant virus detection (Gugerli & Fries, 1983;Diaco et al, 1984;Hill et al, 1984) as well as serological differentiation (Briand et al, 1982;Diaco et al, 1983;Gugerli & Fries, 1983 ;Halk et al, 1984;Hsu et al, 1984). The objectives of this research were to prepare a highly sensitive, non-isotopic, M-Ab-based immunoassay that could be used to detect SMV antigen in infected seeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the fact that no advantage was seen in using a capture antibody différent from that used as detecting antibody may reflect the same multideterminant nature of the epitope on the virus. Using a solid phase radioimmunoassay, Hill et al (1984) found that for diagnosis of soybean mosaic virus, an assay using the same monoclonal antibody for coating and tritium labelling, lacked sensitivity compared to a combination using différent epitope spécifie monoclonal antibodies for capture and détection. However, the nature of the spécifie binding site of the monoclonal antibody used in the single antibody assay was not reported and may hâve been against an infrequent détermi-nant.…”
Section: Discussionmentioning
confidence: 99%